2018
DOI: 10.21037/jss.2018.03.03
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and complications of the use of Gardner-Wells Tongs: a systematic review

Abstract: We conducted a thorough review of the literature to examine the risks and complications associated with the use of Gardner-Wells Tongs (GWT). Twenty-three articles were included in this review for final analysis. One article reported a 37.5% (6/16) incidence rate of minor complications with the usage of GWTs, which included pin loosening, asymmetrical pin positioning, and superficial infections. Various cases reported more serious yet rare complications, including perforation of the skull, brain abscesses, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 24 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…In this study, we applied Garden-Well tongs to reduce dislocation. The application of Garden-Well tongs as a treatment for cervical spine injury has been documented in a study by Saleh et al with a low rate of complications such as pin loosening, the asymmetrical position of the pin, and superficial infection [14] . However, the lower pull-out strength of tongs and progressive decrease of the pull-out strength of tongs made halo traction more preferred.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we applied Garden-Well tongs to reduce dislocation. The application of Garden-Well tongs as a treatment for cervical spine injury has been documented in a study by Saleh et al with a low rate of complications such as pin loosening, the asymmetrical position of the pin, and superficial infection [14] . However, the lower pull-out strength of tongs and progressive decrease of the pull-out strength of tongs made halo traction more preferred.…”
Section: Discussionmentioning
confidence: 99%
“…24 A 2018 systematic review concluded that GWTs are a safe form of skeletal traction with a low rate of complications, most of which are minor, transient, and can be easily managed. 25 A recent 2022 meta-analysis showed that neurological complications were observed in approximately 1.5% of patients undergoing HGT. 4 These complications mainly consisted of transient paresthesia, nystagmus, and dizziness.…”
Section: Discussionmentioning
confidence: 99%
“…Cervical traction stabilizes the head in an optimally reduced extension position and prevents any rotation. Elevation of the head end of the table, which acts as counter traction, helps to reduce venous engorgement in the operative field [9]. Complications of Cervical Traction include bleeding from the temporal artery, pressure sore on the skull (hence a downwards vector to rope is to be avoided), sepsis-from the skin to subdural abscess, Worsening neurological status, squint from 6th cranial nerve fallout [10].…”
Section: Discussionmentioning
confidence: 99%